2018
DOI: 10.1111/1752-1688.12714
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Controls on Watershed Reference Evapotranspiration Varied during 1961–2012 in Southern China

Abstract: Reference evapotranspiration (ETo) is an important hydrometeorological term widely used in understanding and projecting the hydrological effects of future climate and land use change. We conducted a case study in the Qinhuai River Basin that is dominated by a humid subtropical climate and mixed land uses in southern China. Long‐term (1961–2012) meteorological data were used to estimate ETo by the FAO‐56 Penman–Monteith model. The individual contribution from each meteorological variable to the trend of ETo was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 73 publications
(200 reference statements)
5
20
0
Order By: Relevance
“…The consistent trends between ET with each land use type and ET o demonstrated that meteorological factors were controlling factors for ET at the pixel scale. However, we showed that watershed-level ET had a significant decreasing trend in the QRB, coincident with previous studies [2,42]. This was in contrast to the global warming trend and ET was expected to increase under increasing air temperature in the study region [73][74][75].…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentssupporting
confidence: 89%
See 1 more Smart Citation
“…The consistent trends between ET with each land use type and ET o demonstrated that meteorological factors were controlling factors for ET at the pixel scale. However, we showed that watershed-level ET had a significant decreasing trend in the QRB, coincident with previous studies [2,42]. This was in contrast to the global warming trend and ET was expected to increase under increasing air temperature in the study region [73][74][75].…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentssupporting
confidence: 89%
“…Du et al [6] quantified the effects of urbanization on flood events using the Hydrologic Engineering Center's Hydrologic Modeling System (HEC-HMS) for the same study area and found that the stream peak-flow of eight selected floods increased from 2.3% to 13.9% when urban built-up areas increased from 3% in 1988 to 31% in 2018. [29,32,33] As the only common term between surface energy balance and hydrological cycle, ET is a critical process to understand the impacts of LULC change on the hydrology and local climate in the QRB [2,[41][42][43]. However, some of these previous regional studies during the past decade focused on reference evapotranspiration rate (ET o ), which only represented the atmospheric evaporating capability of a hypothetical reference vegetated field [16].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the aerodynamic component explained most of the interannual variability and temporal trends in AED and suggested an increase in AED in arid and semi‐arid regions associated to increased VPD. Several recent studies support stronger aerodynamic control on recent trends in AED, with special focus on the influence of RH (Jerszurki, de Souza, & Silva, ; Johnson & Sharma, ; Qin, Hao, Sun, Liu, & Sun, ; Stephens et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, López‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, Morán‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ). Other studies also suggest generalized decrease in RH in mid‐latitude regions (Vicente‐Serrano, Nieto, et al, ; Willett et al, ), with a resulting impact in AED trends (Stephens et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, López‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, Morán‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ; Vicente‐Serrano et al, ).…”
Section: Aed‐related Drought Trendsmentioning
confidence: 95%
“…Moreover, Cong et al [ 23 ] and Zhang et al [ 24 ] both found the increased ET o along with the rising air temperature throughout the whole China after 1980. In recent years, based on the updated meteorological data, some studies have presented a view that the ET o has had different change points regionally [ 25 , 26 ], which may impact the spatiotemporal characteristics of the “evaporation paradox” in different regions of China.…”
Section: Introductionmentioning
confidence: 99%